Trade liberalisation in T&C: an overview of the welfare effects. (27th August 2010) - Dadakas, Dimitrios; Katranidis, Stelios
The objective of this paper is to examine the effects that trade liberalisation in Textiles and Clothing (T&C) had on the welfare of European producers of cotton-yarn. We employ multi-market theory and a single-market approach to examine the price-induced welfare effects in four major European T&C producing countries namely, Greece, Portugal, Spain and Turkey. Results show that the liberalisation of trade had a substantial negative impact on producers' welfare in all four countries. Welfare and sensitivity analysis suggests that, while cotton-yarn price-decreases and labour-cost increases are expected to further dampen producers' welfare, the adoption of new technologies can substantially assist the competitiveness of European products in the world markets.